High brilliance γ-ray generation from the laser interaction in a carbon plasma channel - Heppe, Christian; Kumar, Naveen (Frontiers in Physics, 2022)
The generation of collimated, high brilliance $γ$-ray beams from a structured plasma channel target is studied by means of 2D PIC simulations. Simulation results reveal an optimum laser pulse pulse duration of $20\,\text{fs}$, for generating $γ$-photon beams of brilliances up to $10^{20}\,\text{s}^{-1}\text{mm}^{-1}\text{mrad}^{-2}\,(0.1\,%\text{BW})^{-1}$ and photon energies well above $200$ MeV in the interaction of an ultra-intense laser (incident laser power $ P_L ≥ 5$ PW) with a high-Z carbon structured plasma target. These results are aimed at employing the upcoming laser facilities with multi-petawatt (PW) laser powers to study the laser-driven nonlinear quantum electrodynamics processes in an all-optical laboratory setup.